Utilization of Media in Increasing Students' Interest in Learning SKI Lessons at MI Al-Baqiyatussholihat - Wasilah (MANDAILING GLOBAL EDUKASIA, 2024)
One of the triggers for the lack of student achievement in SKI lessons is the lack of interest in learning students in the subject. In this case, the researcher wants to solve this problem by using several media as learning support in increasing student interest in learning. And in this study, the researcher used Classroom Action Research which aims to increase student interest in learning SKI subjects. The results of this study indicate that the learning outcomes of class III students of MI Al-Baqiyatussholihat in the first cycle stage are still in the low category, but in the second cycle stage, many changes have been shown by students using a learning approach using audio and video media prepared by the researcher who is also a teacher of the subject of Islamic Cultural History (SKI).